Clade I or clade II? Targeting essential viral genes to differentiate monkeypox virus clades by multiplex real-time PCR - Probert, William S.; Espinosa, Alex; Hacker, Jill K. (Frontiers in Public Health, 2025)
The increasing incidence and global spread of mpox have prompted the World Health Organization to twice declare a Public Health Emergency of International Concern. Sustained human-to-human transmission, largely through sexual contact, and waning population immunity to smallpox have accelerated monkeypox virus evolution and driven the emergence of variants that can adversely affect the performance of existing molecular diagnostic tests. To minimize the risk of PCR target drop out and better detect and monitor emerging monkeypox virus variants, we have developed and validated a multiplex real-time PCR (MpoxEG4-plex rPCR) targeting highly conserved and essential orthopoxvirus genes for the detection of four analytes: orthopoxviruses, monkeypox virus, clade I monkeypox virus, and clade II monkeypox virus. The assay limit of detection was ≤ 9 genome copies per reaction, and the clinical accuracy, sensitivity, and specificity were > 96% for each analyte. The new assay was implemented to help confirm the first case of clade I mpox in the United States. The MpoxEG4-plex rPCR offers an accurate, informative, and reliable molecular diagnostic test for identifying cases and tracking case contacts in support of public health efforts to prevent and control the spread of mpox.